Are patients afraid to go home? Disposition preferences after transient ischaemic attack and minor stroke. Issue 8 (28th January 2020) - Chang, Bernard P; Cornelius, Talea; Willey, Joshua; Edmondson, Donald; Elkind, Mitchell SV; Kronish, Ian M
Abstract : Background: Recent evidence suggests clinical equipoise for managing transient ischaemic attack and minor stroke (TIAMS) either via discharge from the emergency department (ED) with rapid outpatient follow-up or inpatient admission. Understanding patient preferences may guide decision-making around disposition after TIAMS that can lead to higher patient satisfaction and adherence. Psychological distress, particularly a sense of vulnerability (eg, 'threat perception') is associated with adverse psychological outcomes following TIAMS and may influence patient disposition preference. We hypothesised patients with higher threat perceptions in the ED would prefer inpatient admission versus early discharge with rapid outpatient follow-up. Methods: This was a planned secondary analysis of a prospective observational cohort study of ED patients with suspected TIAMS (defined as National Institutes of Health Stroke Scale (NIHSS) score of ≤5). Patients reported disposition preferences and completed a validated scale of threat perception while in the ED (score range: 1–4). Results: 147 TIAMS patients were evaluated (mean age: 59.7±15.4, 45.6% female, 39.5% Hispanic, median NIHSS=1, IQR: 0, 3). A majority of patients (98, 66.7%) preferred inpatient admission compared with discharge from the ED. Overall threat scores were median 1.0 (IQR: 0.43, 1.68). Those preferring admission had similar threat scores compared with those who preferred early disposition (median: 1.00, IQR: 0.43, 1.57) versus 1.00, (IQR: 0.49, 1.68); p=0.40). In a model adjusted for demographic characteristics, threat perceptions remained unassociated with disposition preference. Conclusion: Overall, two-thirds of TIAMS patients preferred inpatient admission over discharge. Disposition preference was not associated with higher threat perception in the ED. Further research examining potential drivers of patient disposition preferences may inform patient discussions and optimise patient satisfaction.